Effect of Yttrium on the microstructure, phase transformation and superelasticity of a Ti–Ni–Cu shape memory alloy. (July 2020) - Zhao, Guangwei; Chen, Jian; Ding, Chong; Fang, Dong; Huang, Caihua; Ye, Xicong
Abstract: The purpose of this work is to systematically investigate the effect of substituting Yttrium for Ti on the microstructure, phase transformation and superelasticity of Ti50 Ni44 Cu6 alloys. The results show that a single-step martensitic transformation occurs in all the selected Ti–Ni–Cu–Y alloys. With increasing Yttrium content, the transformation temperatures first increase approximately by 10–15 °C and then decreases slowly. In the cyclic compression experiments of pre-strain from 2% to 10%, the main reason for the increase of the residual strain is the plastic deformation of the alloys caused by the increasing pre-strain. In the cyclic compression experiments of 5% fixed pre-strain, the recovery rate and the total recoverable strain can be effectively improved to 92.4–96.6% and 4.6–4.83%, respectively. With increasing cycles, as the formation of stress-induced martensite is precluded by high density dislocations, the superelasticity-dominated recovery transforms to elasticity-dominated recovery, which may lead to the gradual decrease of residual strain. In the two kinds of cyclic compression experiments, the results show that the alloys with higher Y content normally have better superelasticity. Highlights: Single-step B2⇋B19′ martensitic transformation occurred in the selected Ti–Ni–Cu–Y alloys. Residual strain increases gradually in cyclic compression experiment with increased pre-strain. The recovery rate can be improved by cyclic compression experiment with fixed pre-strain. The alloys with higher Y content normally have better SE properties.